2017
DOI: 10.5152/ucd.2016.3573
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of contrast-enhanced CT with diffusion -weighted MRI in the Evaluation of patients with acute biliary pancreatitis

Abstract: INTRODUCTIONAcute pancreatitis progresses on an instable course that has exacerbations and remissions. The mortality rate is between 2.1% and 7.8%. Development of necrosis increases mortality in pancreatitis. In patients with necrosis, the mortality rate increases up to 25% (1, 2). Contrast-enhanced computed tomography (CT) is the most important imaging technique to determine the severity of pancreatitis. However, recent studies suggest that the contrast agent for CT aggravates pancreatitis and provokes organ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
(10 reference statements)
0
2
0
Order By: Relevance
“…Therefore, the judgment of the degree of pancreatic parenchymal necrosis is not comprehensive enough, which may affect the prediction efficiency. [23] On the basis of Balthazar CT, the combined detection of necrotic volume and average attenuation value can reasonably reflect the overall degree of pancreatic and peripancreatic necrosis and improve the prediction accuracy, so the combined detection of AUC is higher.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the judgment of the degree of pancreatic parenchymal necrosis is not comprehensive enough, which may affect the prediction efficiency. [23] On the basis of Balthazar CT, the combined detection of necrotic volume and average attenuation value can reasonably reflect the overall degree of pancreatic and peripancreatic necrosis and improve the prediction accuracy, so the combined detection of AUC is higher.…”
Section: Discussionmentioning
confidence: 99%
“…At present, the commonly used diagnostic modality for this disease is biochemical index examination combined with hematuria amylase expression, but it has a certain rate of missed diagnosis (5). CT and MRI are commonly used in clinical imaging diagnosis, both of which can clearly show the changes of pancreatic morphology, surrounding tissue and peritoneal effusion in patients with acute pancreatitis (6). A study by Bieliuniene et al (7) showed that MRI has higher recognition of pancreatic enlargement, especially in the display of peripancreatic effusion and pancreatic contour, due to the special composition of acini and glandular ducts, soft texture and pancreatic juice in pancreas.…”
Section: Introductionmentioning
confidence: 99%